Smokey : The True Stories behind the University of Tennessee's Beloved Mascot - Mattingly, Thomas J. (Book collections on Project MUSE., 2012)
"This book will present the story of the origins of Tennessee's iconic mascot, Smokey, who made his first appearance in 1953. It also examines his role in the broader story of the Athletics Department and the culture of the University and presents often humorous anecdotes about the succeeding generations of the nine dogs that have howled on UT's sidelines"--